2018
DOI: 10.1016/j.revpalbo.2018.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Last Neanderthals in the warmest refugium of Europe: Palynological data from Vanguard Cave

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 152 publications
(26 reference statements)
2
22
0
3
Order By: Relevance
“…The Iberian Peninsula, and Gibraltar in particular, are located on one of the extremes of the Neanderthal distribution and are thought to have served as a refuge for Neanderthals during glaciations (25,30). In addition, it has been suggested that Neanderthals may have persisted in Gibraltar thousands of years after they were replaced by modern humans in other parts of Eurasia (24,25).…”
Section: Significancementioning
confidence: 99%
“…The Iberian Peninsula, and Gibraltar in particular, are located on one of the extremes of the Neanderthal distribution and are thought to have served as a refuge for Neanderthals during glaciations (25,30). In addition, it has been suggested that Neanderthals may have persisted in Gibraltar thousands of years after they were replaced by modern humans in other parts of Eurasia (24,25).…”
Section: Significancementioning
confidence: 99%
“…Finally, current evidence shows that both MIS 5 and MIS 3 Neanderthals in the central Mediterranean region of Iberia made simple open hearths 35,46,47 and wood-gathering patterns appear to be similar irrespective of glacial, interglacial, stadial or interstadial conditions 18,48,49 .…”
Section: Introductionmentioning
confidence: 66%
“…The toad example is convincing exactly because the species replacement is incomplete, with surviving pure B. spinosus and a slowly moving interspecific hybrid zone available for comparison. Disregarding temporal inequalities, B. spinosus temporarily survived in the very south of Britain just as Neanderthal tribes may have persisted for longest at the southernmost fringe of continental Europe, i.e., the Gibraltar peninsula (Carrión et al, ; Jennings, Finlayson, Fa, & Finlayson, ).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, uncovering traces of introgression, as in case of the H. sapiens -H. neanderthalensis interaction, requires extensive data that may be available in hominin paleogenomics (Fu et al, 2016;Racimo et al, 2015;Sankararaman, Mallick, Patterson, & Reich, 2016) but not in most non-model organisms. Finally, to brush the leaky replacement scenario aside as "human exceptionalism" (Varki, 2016- (Carrión et al, 2018;Jennings, Finlayson, Fa, & Finlayson, 2011). Norway (RJ, SR).…”
Section: Genetic Footprints and Parallels With The Demise Of Homo mentioning
confidence: 99%